Controlling the Morphology and Electrochemical Properties of Electrodeposited Nickel Hexacyanoferrate - Tim Steeger; Raphael L. Streng; Anatoliy Senyshyn; Vadim Dyadkin; Xaver Lamprecht; Roman List; Aliaksandr S. Bandarenka (ChemElectroChem, 2025)
In recent years, Prussian blue analogs (PBAs) have gained significant attention due to their broad applicability. The synthesis routines of this material class have been shown to allow for great tunability by varying the corresponding parameters. The control of crystal phase, defect, and water content, as well as electrochemical properties, have been studied extensively for the state‐of‐the‐art coprecipitation method. In turn, electrochemical deposition, which is particularly suited for thin‐film production, remains mainly underexplored. This study investigates the effects of synthesis temperature, scan rate, precursor concentration, and supporting electrolyte pH on nickel hexacyanoferrate (NiHCF) films electrodeposited onto a high surface area carbon‐based substrate via cyclic voltammetry. Electrochemical analysis and morphological characterization reveal that higher deposition temperatures increase cation‐specific capacity, influence NiHCF coverage, and promote larger, more crystalline structures. Scan rate, precursor concentration, and pH variations further demonstrate the correlation between deposition parameters, crystallite size, and NiHCF structure. These findings highlight the tunability of electrodeposited PBAs for tailored electrochemical performance and morphology.